2022
DOI: 10.1007/s00423-022-02630-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of prophylactic doses of tranexamic acid in reducing hemorrhagic events in sleeve gastrectomy

Abstract: Purpose Laparoscopic sleeve gastrectomy (LSG) is currently the most common bariatric surgery in the world. Although it appears to be a safe treatment for obesity, it is still at risk of complications. The latest literature shows that postoperative bleeding occurs in 2–4% of cases, and up to 3% of cases requires reoperation for hemostasis. The aim of the study is to assess the effect of tranexamic acid (TXA) on hemorrhagic events and the reoperation rate in patients undergoing LSG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The design of the included studies was either RCT, cohort, or non-randomized trial. Appraisal of the cohort studies yielded an overall fair quality [ 18 , 28 ]. Brito and the associated team [ 29 ] conducted a non-randomized trial of overall good quality; the only domain with not-reported data was the inclusion of consecutive patients' domain (Tables 2 , 3 ).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of the included studies was either RCT, cohort, or non-randomized trial. Appraisal of the cohort studies yielded an overall fair quality [ 18 , 28 ]. Brito and the associated team [ 29 ] conducted a non-randomized trial of overall good quality; the only domain with not-reported data was the inclusion of consecutive patients' domain (Tables 2 , 3 ).…”
Section: Reviewmentioning
confidence: 99%
“…Operative time (minutes): Five studies with substantial heterogeneity provided data from 644 patients [ 18 , 21 , 22 , 28 , 29 ] that revealed significantly shorter operative time in the TXA group compared to the control group (MD= -5.84, 95%CI [-9.62, -2.05], P=0.003, I2=73%) (Figure 5 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the causality and pathophysiological mechanism are unclear, TXA use is associated with improvement in clinical outcomes in acute trauma, postpartum hemorrhage and orthopedic surgery (29)(30)(31). In metabolic surgery, around 2%-4% of patients experience bleeding, with 3% requiring reoperation (32). Tranexamic acid has been reported to reduce the incidence of bleeding, surgery duration, hospital length of stay, without increasing thromboembolic events (32)(33)(34).…”
Section: Minimizing Blood Lossmentioning
confidence: 99%
“…In metabolic surgery, around 2%-4% of patients experience bleeding, with 3% requiring reoperation (32). Tranexamic acid has been reported to reduce the incidence of bleeding, surgery duration, hospital length of stay, without increasing thromboembolic events (32)(33)(34). A metaanalysis suggested that a dose of 1 g of TXA given at anesthetic induction might be as effective as higher doses (35).…”
Section: Minimizing Blood Lossmentioning
confidence: 99%